Teaching Techniques in Teaching English Language: A Study of SMAN 24 Bandung, West Java - Novan Setiawan Nugraha, Deden; Minda Utami, Eristy (International Journal of Psychosocial Rehabilitation, 2020)
The use of appropriate techniques in teaching is a significant factor that determines the success of learning. The choice of good teaching technique can encourage the students to learn well. In the implementation in the classroom, the use of technique in teaching is always related to the transfer of suitable materials that can interest and motivate students in learning English. The use of teaching technique is also related to the evaluation technique that is used to measure the effectiveness of the teaching itself, and it can be proved by seeing the students ability in speaking English. The researcher tries to find out and describes the teaching techniques used by the teacher of SMAN 24 Bandung in teaching speaking. Based on the data obtained, researchers found out that there are some techniques that are used by teachers. The teacher uses the techniques, material, and evaluation techniques that have been provided in the text books. The teachings used are role playing, story telling, games, group work, pair work, and retelling. The materials are taken from the text books and other sources.Based on the result of the research, the researcher concludes basically that the English teacher has known the teaching techniques. However, in the classroom implementation, it seems to have further improvement. In using teaching materials, teachers only provided limited English text books. Teacher only use teaching sources available in the library and teacher its selft.